Bifunctional electro-catalytic performances of CoWO4 nanocubes for water redox reactions (OER/ORR). Issue 72 (25th September 2017) - AlShehri, Saad M.; Ahmed, Jahangeer; Ahamad, Tansir; Arunachalam, Prabhakarn; Ahmad, Tokeer; Khan, Aslam
Abstract : In this paper, we report the synthesis of cube shaped nanoparticles of CoWO4 (∼30 nm) by molten salts and their bifunctional electro-catalytic activities in water redox reactions for oxygen evolution and oxygen reduction reactions (OER and ORR). Abstract : In this paper, we report the synthesis of cube shaped nanoparticles of CoWO4 (∼30 nm) by molten salts and their bifunctional electro-catalytic activities in water redox reactions for oxygen evolution and oxygen reduction reactions (OER and ORR). Bifunctional performances of CoWO4 nano-cubes are explored for water electrolysis in an alkaline medium (1.0 M KOH) vs. reversible hydrogen electrode (RHE) under various atmospheres (N2, air and O2 ). Low overpotential ( η 10 = 0.45 V) of CoWO4 nano-cubes is accomplished at the current density of 10 mA cm −2 . Tafel polarization curves (potential vs. log current density) reveal relatively lower slope values for OER (∼82 mV dec −1 ) and ORR (∼68 mV dec −1 ) compared to previous reports. Stability test of electrode materials has been performed using chrono-amperometry (CA) at fixed potential for 500 seconds. Kinetics and mobility of electrons have also been studied during the water redox reactions. Stable nature and enhanced bifunctional electro-catalytic performances of earth abundant CoWO4 electrodes could be used as the replacement of expensive electroactive noble electrode materials (Pt, Ir, Ru etc. ) for water electrolysis (OER and ORR) in near future.